Bacteriophages presence in nature and their role in the natural selection of bacterial populations - Naureen, Zakira; Dautaj, Astrit; Anpilogov, Kyrylo; Camilleri, Giorgio; Dhuli, Kristjana; Tanzi, Benedetta; Maltese, Paolo Enrico; Cristofoli, Francesca; De Antoni, Luca; Beccari, Tommaso; Dundar, Munis; Bertelli, Matteo (Acta Biomedica Atenei Parmensis, 2020)
Phages are the obligate parasite of bacteria and have complex interactions with their hosts. Phages can live in, modify, and shape bacterial communities by bringing about changes in their abundance, diversity, physiology, and virulence. In addition, phages mediate lateral gene transfer, modify host metabolism and reallocate bacterially-derived biochemical compounds through cell lysis, thus playing an important role in ecosystem. Phages coexist and coevolve with bacteria and have developed several antidefense mechanisms in response to bacterial defense strategies against them. Phages owe their existence to their bacterial hosts, therefore they bring about alterations in their host genomes by transferring resistance genes and genes encoding toxins in order to improve the fitness of the hosts. Application of phages in biotechnology, environment, agriculture and medicines demands a deep insight into the myriad of phage-bacteria interactions. However, to understand their complex interactions, we need to know how unique phages are to their bacterial hosts and how they exert a selective pressure on the microbial communities in nature. Consequently, the present review focuses on phage biology with respect to natural selection of bacterial populations.